A production process for preparing polyaspartic acid based on solid superacid

By using solid super acid SO42-/ZrO2-Al2O3 as a catalyst in polyaspartic acid production, the problems of water resource consumption and environmental pollution in traditional methods are solved, and efficient catalysts and reusable catalysts are achieved.

CN119638994BActive Publication Date: 2025-04-25BEIJING YANZHISHAN TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510177035.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-02-18
Publication Date
2025-04-25
Estimated Expiration
2045-02-18

AI Technical Summary

Technical Problem

During the production process of polyaspartic acid, the use of a large amount of acid as a catalyst leads to water resource consumption and environmental pollution, and is difficult to recycle.

Method used

Solid super acid SO42-/ZrO2-Al2O3 with a particle size of 80 mesh is used as a catalyst. Through polymerization reaction under vacuum high temperature conditions, the water washing process is reduced, water resources are saved, and the catalyst utilization efficiency is improved through acid titration and regeneration treatment.

Benefits of technology

The catalytic efficiency is improved, the amount of catalyst is reduced, the discharge of large amounts of acid-containing wastewater and water resource consumption is avoided, and the reusable and regeneration treatment of the catalyst is realized.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119638994B_ABST
    Figure CN119638994B_ABST
Patent Text Reader

Abstract

The invention belongs to the field of preparation of high molecular polymers and discloses a production process for preparing polyaspartic acid based on solid superacid, comprising: using aspartic acid as a raw material, using solid superacid SO4 with a particle size of more than 80 meshes 2‑ / ZrO2-Al2O3 as a catalyst, react under vacuum and high temperature conditions to obtain a polymerization product, crush the polymerization product and screen the particles with a particle size of less than 100 mesh to obtain polysuccinimide, and then put it into an aqueous solution of sodium hydroxide or potassium hydroxide for hydrolysis to obtain a sodium polyaspartate or potassium polyaspartate aqueous solution; filter or electrodialyze the sodium polyaspartate or potassium polyaspartate aqueous solution, and then sterilize and dry to obtain polyaspartic acid. The method uses solid superacid SO4 2‑ / ZrO2‑Al2O3 is used as a catalyst, which saves water resource consumption, simplifies the process route, avoids the treatment process of washing acidic wastewater, and has high catalytic efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of preparation of high molecular polymers, and in particular relates to a production process for preparing polyaspartic acid based on solid superacid. Background Art

[0002] Polyaspartic acid is a homopolymeric amino acid with aspartic acid as the monomer. Each monomer contains a free carboxyl group and a peptide bond. It is a multifunctional biopolymer material with strong moisturizing, chelating, dispersing and adsorption effects. It is widely used in water treatment agents, fertilizer enhancers, metal cutting fluids, daily chemicals, detergents, dispersants, chelating agents and water retaining agents.

[0003] At present, the main synthesis method of polyaspartic acid is: using aspartic acid as raw material, directly obtaining polysuccinimide through high-temperature dehydration polycondensation in the solid phase under the action of catalysts such as phosphoric acid and sulfuric acid; after the polysuccinimide is crushed and washed with water to remove the acid, it is hydrolyzed in an aqueous sodium hydroxide solution to obtain an aqueous solution of sodium polyaspartate. In this polymerization process, since a solid-phase polymerization process is adopted instead of an organic solvent, its production cost is reduced and the pressure of environmental pollution is effectively controlled. However, it still requires a large amount of acid as a catalyst, and both phosphoric acid and sulfuric acid are difficult to recycle, and a large amount of water is required for flushing, resulting in serious consumption of water resources. Summary of the invention

[0004] 1. Purpose of the invention

[0005] The purpose of the present invention is to provide a production process for preparing polyaspartic acid based on solid superacid, which adopts solid superacid SO 4 2- / ZrO 2 -Al 2 O 3 As a catalyst in the polymerization process, it avoids the treatment process of washing acidic wastewater, saves water resource consumption, simplifies the process route, and has higher catalytic efficiency.

[0006] (II) Technical solution

[0007] In order to solve the above problems, the first aspect of the present invention provides a production process for preparing polyaspartic acid based on solid superacid, wherein the solid superacid used is SO 4 2- / ZrO 2 -Al 2 O 3 , including the following steps:

[0008] S1, using aspartic acid as raw material, solid superacid SO with a particle size of 80 mesh or more 4 2- / ZrO 2 -Al 2 O 3 As a catalyst, the polymerization product is obtained by reaction under vacuum and high temperature conditions, and the polymerization product includes polysuccinimide;

[0009] S2, crushing the polymer product and sieving the particles with a particle size of less than 100 mesh to obtain polysuccinimide and placing it in an aqueous solution of sodium hydroxide or potassium hydroxide for hydrolysis to obtain a sodium polyaspartate or potassium polyaspartate aqueous solution;

[0010] S3, filtering or electrodialyzing the aqueous solution of sodium polyaspartate or potassium polyaspartate, and sterilizing and drying the solution after the pH value of the solution drops to 3.8-4.0 to obtain polyaspartic acid.

[0011] Furthermore, the aspartic acid in step S1 and the solid superacid SO 4 2- / ZrO 2 -Al 2 O 3 The mass ratio is 1:0.01~0.1.

[0012] Furthermore, in step S2, the molar ratio of sodium hydroxide or potassium hydroxide to the polysuccinimide repeating unit is 1.2-0.9:1.

[0013] Furthermore, the production process also includes:

[0014] S4, performing acid titration on the particles with a particle size greater than 100 mesh screened out in step S2, comprising:

[0015] If the solid superacid SO 4 2- / ZrO 2 -Al 2 O 3 If the particles can make the indicator color, they are used as the solid superacid SO in step S1. 4 2- / ZrO 2 -Al 2 O 3 The catalyst is used directly;

[0016] If the solid superacid SO 4 2- / ZrO 2 -Al 2 O 3 If the particles cannot make the indicator color, they will be regenerated; the particles with a particle size greater than 100 mesh are solid superacid SO 4 2- / ZrO 2-Al 2 O 3 .

[0017] Furthermore, the regeneration process comprises: regenerating the solid superacid SO 4 2- / ZrO 2 -Al 2 O 3 The particles are calcined in a tube furnace and then added to concentrated sulfuric acid, followed by drying and calcination to obtain a regenerated solid superacid SO 4 2- / ZrO 2 -Al 2 O 3 , solid superacid SO after regeneration 4 2- / ZrO 2 -Al 2 O 3 Can make the indicator color.

[0018] Furthermore, in step S1, the polymerization reaction temperature is 120-220° C., the polymerization reaction time is 1-6 h, and the polymerization reaction pressure is -0.05-0.095 MPa.

[0019] Furthermore, in step S2, the hydrolysis reaction temperature is 30-60° C., the hydrolysis reaction time is 0.5-4 h, and the stirring speed is controlled to be 70-120 r / min.

[0020] Furthermore, solid superacid SO 4 2- / ZrO 2 -Al 2 O 3 The preparation method comprises:

[0021] The nano zirconium hydroxide and pseudo-boehmite are mixed in proportion, and then a binder is added and mixed evenly to obtain a mixed material, wherein the molar ratio of the nano zirconium hydroxide and the pseudo-boehmite is 20-30:1, calculated as Zr and Al respectively;

[0022] Deionized water is added to the mixture, and the mixture is stirred to obtain a mixed slurry, which is processed by a granulator and dried to obtain first particles, wherein the mass ratio of the mixture to the deionized water is 1:1;

[0023] The first particles are added into concentrated sulfuric acid, and the second particles are obtained after being drained and dried;

[0024] The second particle is placed in a muffle furnace and calcined to obtain a solid superacid SO 4 2- / ZrO 2 -Al 2 O3 .

[0025] Furthermore, the binder includes carboxymethyl cellulose and polyethylene glycol 600, and the added amounts of the carboxymethyl cellulose and the polyethylene glycol 600 are both 0.8-1.2 wt %.

[0026] Furthermore, the solid-liquid mass ratio of the first particles to the concentrated sulfuric acid is 1:3-5.

[0027] Furthermore, the filtering methods in step S3 include pipeline filtration, bag filtration, centrifugal filtration and plate pressure filtration, and the pore size of the filter cloth, filter screen or filter bag used is 280-320 mesh, preferably 300 mesh.

[0028] (III) Beneficial effects

[0029] The above technical solution of the present invention has the following beneficial technical effects: the present invention provides a production process for preparing polyaspartic acid based on solid superacid, in which aspartic acid is used as a raw material, and a solid superacid SO 4 2- / ZrO 2 -Al 2 O 3 The catalyst is used to polymerize to obtain a polymerization product, wherein the polymerization product includes polysuccinimide. In this step, a solid superacid SO 4 2- / ZrO 2 -Al 2 O 3 As a catalyst in the polymerization process, solid superacid SO 4 2- / ZrO 2 -Al 2 O 3 The proton density of solid superacid SO is much higher than that of common inorganic acids. Compared with traditional catalysts such as sulfuric acid and phosphoric acid, its catalytic efficiency is higher, so it can reduce the amount of catalyst used and avoid the discharge of a large amount of acid-containing wastewater and the consumption of water resources. 4 2- / ZrO 2 -Al 2 O 3 The solid superacid is prepared according to the method for preparing the solid superacid of the present invention. Then the polymer product is crushed and the particles with a particle size less than 100 mesh are screened. The screening is performed with a 100 mesh screen. The component with a particle size less than 100 mesh is the polymer product polysuccinimide, and the component with a particle size greater than 100 mesh is the solid superacid catalyst. SO 4 2- / ZrO 2 -Al 2 O 3As a catalyst for the polymerization process, it has good mechanical strength and can be separated from the product by simple screening after the polymerization product is crushed. Finally, the polysuccinimide is crushed and hydrolyzed, and then filtered or electrodialyzed. After the pH of the solution is reduced to 3.8-4.0, polyaspartic acid is obtained by sterilization and drying. The solid superacid catalyst with a particle size greater than 100 mesh is screened for acid strength titration. According to the titration result, it can be determined whether it can be used directly. The solid superacid catalyst can be reused at least 7 times, and the failed catalyst can be regenerated, that is, it can be remade according to the solid superacid synthesis process to obtain a solid superacid for recycling. The present invention eliminates the process of washing the polymerization product polysuccinimide with a large amount of water to remove the acid catalyst, saves water resource consumption, simplifies the process route, and avoids the discharge of phosphoric acid-containing wastewater. The method of the present invention can be carried out in large-scale industrial production, and can meet the application of polyaspartic acid and its salt products in the fields of cosmetics, agriculture, boiler water treatment, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 The present invention is a production process flow chart of preparing polyaspartic acid based on solid superacid. DETAILED DESCRIPTION

[0031] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with specific embodiments and with reference to the accompanying drawings. It should be understood that these descriptions are only exemplary and are not intended to limit the scope of the present invention. In addition, in the following description, the description of well-known structures and technologies is omitted to avoid unnecessary confusion of the concept of the present invention.

[0032] The term "polyaspartic acid" used in the present invention is synonymous with "polyaspartic acid" and "polyaspartic acid". The term "polysuccinimide" is synonymous with "polysuccinimide".

[0033] like Figure 1 As shown, the present invention provides a production process for preparing polyaspartic acid based on solid superacid, wherein the solid superacid is SO 4 2- / ZrO 2 -Al 2 O 3 , including the following steps:

[0034] S1, using aspartic acid as raw material, solid superacid SO with a particle size of 80 mesh or more 4 2- / ZrO 2 -Al 2 O 3The solid superacid catalyst is sulfated zirconium oxide-aluminum oxide, i.e. SO 4 2- / ZrO 2 -Al 2 O 3 . Wherein aspartic acid and the solid superacid SO 4 2- / ZrO 2 -Al 2 O 3 The mass ratio of is 1:0.01~0.1. In the step S1, the polymerization temperature is 120~220°C, preferably 170~200°C, the polymerization time is 1~6h, preferably 2~4h, and the polymerization pressure is -0.05~-0.095MPa. The polysuccinimide is also doped with a solid superacid SO 4 2- / ZrO 2 -Al 2 O 3 catalyst.

[0035] S2, crushing the polymer product and sieving the particles with a particle size less than 100 mesh to obtain polysuccinimide and placing it in an aqueous solution of sodium hydroxide or potassium hydroxide for hydrolysis to obtain a sodium polyaspartate or potassium polyaspartate aqueous solution. Wherein, the molar ratio of sodium hydroxide or potassium hydroxide to the polysuccinimide repeating unit is 1.2~0.9:1. This step is screened with a 100-mesh sieve, and the component with a particle size less than 100 mesh is the polymer product polysuccinimide, and the component with a particle size greater than 100 mesh is a solid superacid catalyst. The temperature of the hydrolysis reaction is controlled to be 30~60°C; the time of the hydrolysis reaction is 0.5~4h, preferably 1~2h; the stirring speed during the hydrolysis reaction is 70~120rpm.

[0036] S3, filtering or electrodialyzing the aqueous solution of sodium polyaspartate or potassium polyaspartate, and sterilizing and drying the solution after the pH value of the solution drops to 3.8-4.0 to obtain polyaspartic acid. In step S2, the hydrolysis reaction temperature is 30-60°C, the hydrolysis reaction time is 0.5-4h, and the stirring speed is controlled to be 70-120r / min. The filtering methods include pipeline filtration, bag filtration, centrifugal filtration, plate pressure filtration, etc., and the pore size of the filter cloth, filter screen or filter bag is 300 mesh.

[0037] Furthermore, the production process also includes:

[0038] S4, performing acid titration on the particles with a particle size greater than 100 mesh screened out in step S2, comprising:

[0039] If the solid superacid SO4 2- / ZrO 2 -Al 2 O 3 If the particles can make the indicator color, they are used as the solid superacid SO in step S1. 4 2- / ZrO 2 -Al 2 O 3 The catalyst is used directly. The acid strength of the catalyst in the present invention can be determined by referring to the contents and steps of the titration method in Chapter 8 of "Analysis, Test and Characterization of Industrial Catalysts" edited by Liu Xiyao et al., and the Hammett indicator is m-nitrotoluene (pKa = -11.99). The acidity index requirement of the solid superacid catalyst in the present invention is that the indicator can show an acid color (yellow) during titration, that is, the Hammett acidity function Ho <-11.99. If the solid superacid SO 4 2- / ZrO 2 -Al 2 O 3 If the particles can make the indicator m-nitrotoluene show an acid color (yellow), the process directly proceeds to step S1 for catalytic polymerization.

[0040] If the solid superacid SO 4 2- / ZrO 2 -Al 2 O 3 If the particles cannot make the indicator color, they will be regenerated. 4 2- / ZrO 2 -Al 2 O 3 If the particles cannot make the indicator m-nitrotoluene show acid color (yellow), they are regenerated. The regeneration process includes: regenerating the solid superacid SO 4 2- / ZrO 2 -Al 2 O 3 The particles are calcined in a tube furnace and then added to concentrated sulfuric acid, followed by drying and calcination to obtain a regenerated solid superacid SO 4 2- / ZrO 2 -Al 2 O 3 The regenerated solid superacid SO 4 2- / ZrO 2 -Al 2 O 3Can make the indicator color.

[0041] Furthermore, the solid superacid SO 4 2- / ZrO 2 -Al 2 O 3 The preparation method comprises:

[0042] (1) Mixing nano zirconium hydroxide and pseudo-boehmite in proportion, and then adding a binder and mixing evenly to obtain a mixed material, wherein the nano zirconium hydroxide and pseudo-boehmite are respectively calculated as Zr and Al, and the molar ratio is 20-30:1. The binder comprises carboxymethyl cellulose and polyethylene glycol 600, and the added amount of the carboxymethyl cellulose and the polyethylene glycol 600 is 0.8-1.2wt%, and the preferred added amount of the carboxymethyl cellulose and the polyethylene glycol 600 is 1wt%.

[0043] (2) adding deionized water to the mixture, stirring to obtain a mixed slurry, treating the mixed slurry with a granulator, obtaining particles with a particle size of about 40 mesh by the granulator, and drying at 120° C. to constant weight to obtain first particles, wherein the mass ratio of the mixed material to the deionized water is 1:1;

[0044] (3) After soaking the first particles in concentrated sulfuric acid for 2 hours, draining the excess liquid, and drying at 120°C to obtain second particles (acidic particles). The solid-liquid mass ratio of the first particles to the concentrated sulfuric acid is 1:3-5;

[0045] (4) The second particle was placed in a muffle furnace and calcined under the following conditions: calcined at 650°C for 3 h in a static air atmosphere at a heating rate of 5°C / min to obtain a solid superacid SO 4 2- / ZrO 2 -Al 2 O 3 Finally, the particles with a particle size of >80 mesh are obtained through screening and enter step S1 for catalysis.

[0046] The following is described in detail in conjunction with specific embodiments:

[0047] Calculation method: The method for detecting the purity (i.e., polymerization reaction rate) of polysuccinimide in the present invention is: accurately weigh 1.00 g of polysuccinimide product, place it in 20.0 mL of N,N-dimethylformamide, and stir it at 60°C to dissolve it; the dissolved solution is filtered with a sand core funnel, and the sand core funnel and the filtered insoluble matter are dried at 120°C for more than 4 hours until the mass no longer changes. The calculation formula for the purity of polysuccinimide is:

[0048] ; (1)

[0049] In formula (1), m 1 is the total weight of the sand core funnel and insoluble matter after filtration and drying, m 0 is the weight of the sand core funnel before filtration, and M is the total weight of the polysuccinimide product sample.

[0050] In addition, the present invention adopts liquid chromatography to detect the molecular weight of polyaspartic acid or its salt by liquid chromatograph (Shimadzu LC-20A), which is expressed as number average molecular weight (M n ).

[0051] The method for detecting the molecular weight of polysuccinimide in the present invention is as follows: polysuccinimide, sodium hydroxide and water are mixed in a mass ratio of 1:0.045:3, and the mixture is stirred at room temperature for 2 h, and then the solution is analyzed according to the molecular weight detection method of polyaspartic acid or its salt, and the molecular weight of the polyaspartic acid obtained by the detection is calculated according to the formula The molecular weight of polysuccinimide was converted to number average molecular weight (Mn).

[0052] In the present invention, the yield calculation method of aspartic acid solid phase polymerization reaction is: Y=W 1 / W 2 .

[0053] Among them, W 1 is the mass of the polysuccinimide solid particles obtained after polymerization, crushing and screening, W 2 is the mass of the raw material aspartic acid. Since the polymerization of aspartic acid to obtain polysuccinimide is a condensation reaction, in which each molecule of aspartic acid loses two molecules of water on average, the maximum yield of complete reaction is theoretically 72.93%.

[0054] Example

[0055] 1.1 Preparation of solid superacid catalyst

[0056] Solid superacid SO 4 2- / ZrO 2 -Al 2 O 3 The preparation method comprises:

[0057] (1) Accurately weigh 250.00 g of nano-zirconium hydroxide, 5.10 g of powdered pseudo-boehmite, 2.55 g of carboxymethyl cellulose, and 2.55 g of polyethylene glycol 600 to obtain a mixed material. The molecular formula of pseudo-boehmite is: Al 2 O 3 ·nH 2 O, n is 0.08-0.62, and the molar ratio of nano zirconium hydroxide and pseudo-boehmite is 20-22:1, calculated as Zr and Al respectively.

[0058] (2) The mixed material was placed in a beaker and 260.2 g of deionized water was added, and then mechanically stirred at room temperature to obtain a slurry. The slurry was granulated with a small granulator and the particle size was controlled to be about 40 mesh, and then dried in a forced air drying oven at 120° C. to constant weight to obtain the first granules.

[0059] (3) After the first particles were immersed in 1000 g of concentrated sulfuric acid and allowed to stand for 2 h, the excess concentrated sulfuric acid was drained with a sand core funnel under normal pressure. The sand core funnel and the material were placed in a forced air drying oven and dried at 120°C for 12 h to obtain the second particles; the solid-liquid mass ratio of the first particles to the concentrated sulfuric acid was 1:3.8 (i.e., 260.2:1000).

[0060] (4) The dried second particles were transferred to a ceramic cup and calcined in a muffle furnace at 650 °C for 3 h (heating rate of 5 °C / min) under a static air atmosphere to obtain a solid superacid SO 4 2- / ZrO 2 -Al 2 O 3 , use a sieve to screen the solid superacid SO with a particle size of 80 mesh or more 4 2- / ZrO 2 -Al 2 O 3 As a catalyst for the preparation of polyaspartic acid. In the determination of acid strength, titration can cause the indicator m-nitrotoluene to change from colorless to yellow, that is, the Hammett acidity function Ho <-11.99.

[0061] 1.2 Preparation of polysuccinimide

[0062] Aspartic acid was used as the raw material, and the solid superacid SO with a particle size of 80 mesh or more screened in the preparation method of step 1.1 was used. 4 2- / ZrO 2 -Al 2 O 3 The optimal process conditions were obtained by orthogonal analysis of three factors and three levels, with the polymerization temperature, polymerization time and the amount of solid superacid catalyst as variables. Specifically, 300.0 g of aspartic acid and 3.0, 15.0 and 30.0 g of SO 4 2- / ZrO 2 -Al 2 O 3The catalyst (mass ratio of aspartic acid to solid superacid was 1:0.01 (C1), 0.05 (C2), 0.1 (C3) respectively) was placed in a 2 L vacuum reactor, and after being evacuated to below -0.08 MPa under mechanical stirring, the temperature was raised to 120°C (A1), 180°C (A2), 220°C (A3) and maintained for 1h (B1), 3h (B2), 6h (B3), respectively, to obtain a light yellow to yellow solid polymerization product (polysuccinimide doped solid superacid catalyst particles). The orthogonal setting of the process conditions is shown in Table 1, and the orthogonal analysis with reaction rate and molecular weight as the results is also shown in Table 1.

[0063] Table 1 Orthogonal experimental design and results

[0064]

[0065] Table 2 Analysis of reaction rate results

[0066]

[0067] Table 3 Molecular weight analysis

[0068]

[0069] As shown in Table 2, in the orthogonal analysis with reaction rate as the result, the best process condition combination A3B3C3 can be obtained by calculating the mean values, namely: temperature 220℃, time 6 h, catalyst dosage 30.0 g; and by F 0.05 It can be seen that the three factors are significant factors. The orthogonal analysis in Table 3 with molecular weight as the result is consistent with the conclusion in Table 2.

[0070] 1.3 Preparation of polysuccinimide under optimal process conditions (A3B3C3 combination)

[0071] 300.0 g aspartic acid and 30.0 g SO 4 2- / ZrO 2 -Al 2 O 3The catalyst (above 80 mesh particle size) was placed in a 2 L vacuum reactor (mass ratio of aspartic acid to catalyst was 1:0.1), and after being evacuated to below -0.08 MPa under mechanical stirring, the temperature was raised to 220°C and maintained for 6 h to obtain a yellow solid. The yellow solid was crushed in batches using a small Chinese medicine grinder, and 215.50 g of solid particles with a particle size of less than 100 mesh (polysuccinimide, i.e., a yield of 71.83%) and 31.02 g of solid particles with a particle size of >100 mesh were screened out using a 100 mesh screen. The polymerization results are shown in Example 10 in Table 4. At the same time, multiple parallel experiments for the preparation of polysuccinimide were carried out continuously according to the experimental conditions in 1.3 (the catalysts were all newly prepared to ensure the parallelism of the experiments), and the results are shown in Examples 11-16 in Table 4. As can be seen from Table 4, the RSDs of the reaction rate and yield are both less than 1%, and the molecular weight M n The RSD was less than 10%, indicating that the reaction process had good stability after repeated repetitions.

[0072] Table 4 Preparation of polysuccinimide

[0073]

[0074] 1.4 Solid superacid SO 4 2- / ZrO 2 -Al 2 O 3 Reuse of catalyst

[0075] According to the experimental conditions in step 1.3 above, multiple experiments on the preparation of polysuccinimide were carried out continuously to determine the SO 4 2- / ZrO 2 -Al 2 O 3 The effect of repeated use of the catalyst was verified, and the catalyst added each time was the recycled product of the catalyst used in the previous test. The results are shown in Table 5. It can be seen that when the continuous experiment was carried out for the 7th time, the Ho value of the catalyst was >-11.99, that is, the acidity dropped to the point where it could not meet the requirements of solid superacid. At the same time, the reaction rate, molecular weight and yield of these 7 experiments maintained good stability.

[0076] Table 5 Solid superacid SO 4 2- / ZrO 2 -Al 2 O 3 Verification of the effect of catalyst reuse

[0077]

[0078] 1.5 Pilot scale-up of solid phase polymerization process

[0079] Referring to the experimental conditions in step 1.3 above, 50.0 kg aspartic acid and 5.0 kg SO 4 2- / ZrO 2 -Al 2 O 3 The catalyst (above 80 mesh particle size) was placed in a 300 L vacuum reactor, and after being evacuated to below -0.08 MPa under mechanical stirring, the temperature was raised to 220 ° C and maintained for 6 h to obtain a yellow solid. The yellow solid was crushed in batches using a dust-free grinder, and 35.19 kg of solid particles with a particle size of <100 mesh (i.e., a yield of 70.38%) and 5.12 kg of solid particles with a particle size of >100 mesh were screened out using a 100 mesh screen. In addition, multiple continuous experiments were carried out according to the above step 1.4, and the results are shown in Table 6. It can be seen that the process described in the present invention has good reproducibility after pilot scale-up, proving that it is suitable for industrial scale-up production.

[0080] Table 6 Pilot preparation results of polysuccinimide

[0081]

[0082] 1.6 Solid superacid SO 4 2- / ZrO 2 -Al 2 O 3 Catalyst regeneration preparation

[0083] Accurately weigh 300.0 g of the solid superacid catalyst after the completion of Example 23 above, transfer it to a graphite boat and place it in a quartz tube of a tube furnace, and heat it to 450°C at a heating rate of 10°C / min under an air flow of 3 L / min and maintain it for 1 h. After naturally cooling to room temperature, 268.3 g of solid is obtained, and it is soaked in concentrated sulfuric acid at a solid-liquid ratio of 1:4 for 2 h, then the excess liquid is drained and dried at 120°C. The dried acidic particles are placed in a muffle furnace and calcined at 650°C for 3 h in a static air atmosphere at a heating rate of 5°C / min to obtain a regenerated solid superacid SO 4 2- / ZrO 2 -Al 2 O 3 , and then sieve it to obtain particles with a particle size of >80 mesh.

[0084] The regenerated solid superacid catalyst was used to prepare polysuccinimide according to the process conditions in step 1.3 above, and the polymerization results are shown in Table 7. It can be seen that the method of the present invention can regenerate the solid superacid catalyst, and the regenerated catalyst does not affect the polymerization reaction results.

[0085] Table 7 Regeneration preparation of solid superacid catalysis results

[0086]

[0087] 1.7 Preparation of polyaspartic acid

[0088] 1.7.1: Preparation of sodium polyaspartate by hydrolysis

[0089] Accurately weigh 2.47 g of NaOH and add it to 30.0 mL of deionized water, stirring to completely dissolve it. Accurately weigh 6.00 g of the polysuccinimide solid prepared in Example 10 above, add it to the above NaOH aqueous solution, stir in a 40°C water bath for 2 h, and the stirring rate is 100 rpm to obtain a yellow-brown transparent liquid, and the molar ratio of sodium hydroxide to polysuccinimide repeating units is 1:1. After filtering with a 300-mesh filter cloth to remove a small amount of residual insoluble matter, a sodium polyaspartate aqueous solution is obtained, and its pH detection is 9.87 (polysuccinimide hydrolysis consumes NaOH, so measuring the pH value can characterize the hydrolysis reaction rate of polysuccinimide). Using the above method, the polysuccinimide solid prepared in Example 10 is used as a sample, and 10 parallel experiments are carried out continuously. The results are shown in Table 8. It can be seen that under this process condition, the hydrolysis reaction stability of polysuccinimide is good.

[0090] Table 8 Preparation of sodium polyaspartate aqueous solution

[0091]

[0092] 1.7.2 Preparation of polyaspartic acid

[0093] Accurately weigh 20.0 kg of the sodium polyaspartate aqueous solution prepared under the experimental conditions of step 1.7.1, and dilute it with 80.0 kg of deionized water. Adjust the diluted solution with phosphoric acid to a pH of 3.81. Use a MWCO 3 kDa filter membrane for ultrafiltration. After the volume and pH value of the retentate are stable, take the retentate, which is the polyaspartic acid aqueous solution, which is a yellow transparent liquid with a pH of 3.96. After sterilization and drying, a light yellow polyaspartic acid powder can be obtained.

[0094] 1.7.3 Preparation of potassium polyaspartate and polyaspartic acid by hydrolysis

[0095] Accurately weigh 3.46 kg of KOH and add it to 30.0 L of deionized water, stirring to completely dissolve it. Accurately weigh 6.00 kg of the polysuccinimide solid prepared in Example 18 in the above step 1.5, add it to the above KOH aqueous solution, stir in a 40°C water bath for 2 h, and the stirring rate is 100 rpm to obtain a yellow-brown transparent liquid, and the molar ratio of potassium hydroxide to polysuccinimide repeating units is 1:1. After filtering out a small amount of residual insoluble matter using a pipeline filter with a 300-mesh filter, a potassium polyaspartate aqueous solution is obtained, and its pH is detected to be 9.76. The obtained potassium polyaspartate aqueous solution is then filtered or electrodialyzed, and after the pH of the solution drops to 3.8~4.0, it is sterilized and dried to obtain a light yellow polyaspartic acid powder.

[0096] The present invention discloses a production process for preparing polyaspartic acid based on solid superacid. In the synthesis process of polyaspartic acid and its salt, solid superacid with suitable particle size is used as a catalyst in the polymerization process. The main advantages thereof include:

[0097] 1. Solid superacid SO 4 2- / ZrO 2 -Al 2 O 3 The proton density of chlorinated polyol is much greater than that of common inorganic acids. As a polymerization catalyst, its catalytic efficiency is higher, which can reduce the amount of catalyst used in the polymerization process.

[0098] 2. SO 4 2- / ZrO 2 -Al 2 O 3 As a catalyst for the polymerization process, it has good mechanical strength. After the polymerization product is crushed, it can be separated from the product by simple screening, and can be directly reused after passing the acid strength titration. Even if the acid strength titration is unqualified, it can be remade into a solid super acid according to the solid super acid synthesis process for recycling.

[0099] 3. The process of washing the polymerization product polysuccinimide with a large amount of water to remove the acid catalyst is omitted, which saves water resource consumption, simplifies the process route, and avoids the discharge of phosphoric acid-containing wastewater.

[0100] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.

Claims

1. A production process for preparing polyaspartic acid based on solid superacid, characterized in that: The solid superacid is SO4 2- / ZrO2-Al2O3, comprising the following steps: S1, using aspartic acid as raw material, solid superacid SO4 with a particle size of more than 80 mesh 2- / ZrO2-Al2O3 is used as a catalyst, and a polymerization product is obtained by reaction under vacuum and high temperature conditions. The polymerization product includes polysuccinimide. The aspartic acid in step S1 and the solid superacid SO4 2- The mass ratio of / ZrO2-Al2O3 is 1:0.01~0.1, the polymerization temperature is 120~220℃, the polymerization time is 1~6h, and the polymerization pressure is -0.05~-0.095MPa; S2, crushing the polymer product and sieving particles with a particle size of less than 100 mesh to obtain polysuccinimide and placing it in an aqueous solution of sodium hydroxide or potassium hydroxide for hydrolysis to obtain a sodium polyaspartate or potassium polyaspartate aqueous solution; S3, filtering or electrodialyzing the aqueous solution of sodium polyaspartate or potassium polyaspartate, sterilizing and drying to obtain polyaspartic acid.

2. The production process for preparing polyaspartic acid based on solid superacid according to claim 1, characterized in that: In the step S2, the molar ratio of the sodium hydroxide or the potassium hydroxide to the polysuccinimide repeating unit is 1.2-0.9:

1.

3. The production process for preparing polyaspartic acid based on solid superacid according to claim 1, characterized in that: The production process also includes: S4, performing acid titration on the particles with a particle size greater than 100 mesh screened out in step S2, comprising: If the solid superacid SO4 is screened out 2- / ZrO2-Al2O3 particles can make the indicator color, so it is used as the solid superacid SO4 in step S1 2- / ZrO2-Al2O3 catalyst is used directly; If the solid superacid SO4 is screened out 2- / ZrO2-Al2O3 particles cannot make the indicator color, so they are regenerated; wherein the particles with a particle size greater than 100 mesh are solid superacid SO4 2- / ZrO2-Al2O3.

4. The production process for preparing polyaspartic acid based on solid superacid according to claim 3, characterized in that: The regeneration process comprises: treating the solid superacid SO4 to be regenerated 2- / ZrO2-Al2O3 particles are calcined in a tube furnace and then added to concentrated sulfuric acid, followed by drying and calcination to obtain regenerated solid superacid SO4 2- / ZrO2-Al2O3, the solid superacid SO4 after the regeneration treatment 2- / ZrO2-Al2O3 can make the indicator show color.

5. The production process for preparing polyaspartic acid based on solid superacid according to claim 1, characterized in that: In the step S2, the hydrolysis reaction temperature is 30-60° C., and the hydrolysis reaction time is 0.5-4 h.

6. The production process for preparing polyaspartic acid based on solid superacid according to claim 1, characterized in that: The solid superacid SO4 2- The preparation method of ZrO2-Al2O3 comprises: The nano zirconium hydroxide and pseudo-boehmite are mixed in proportion, and then a binder is added and mixed evenly to obtain a mixed material, wherein the nano zirconium hydroxide and pseudo-boehmite are respectively calculated as Zr and Al, and the molar ratio is 20-30:1; Adding deionized water to the mixture, stirring to obtain a mixed slurry, treating the mixed slurry with a granulator, and drying the mixed slurry to obtain first particles, wherein the mass ratio of the mixture to the deionized water is 1:1; Adding the first particles into concentrated sulfuric acid, draining and drying to obtain second particles; The second particles are placed in a muffle furnace and calcined to obtain solid superacid SO4 2- / ZrO2-Al2O3.

7. The production process for preparing polyaspartic acid based on solid superacid according to claim 6, characterized in that: The binder includes carboxymethyl cellulose and polyethylene glycol 600, and the added amounts of the carboxymethyl cellulose and the polyethylene glycol 600 are both 0.8-1.2 wt %.

8. The process for preparing polyaspartic acid based on solid superacid according to claim 6, characterized in that: The solid-liquid mass ratio of the first particles to concentrated sulfuric acid is 1:3-5.

Citation Information

Patent Citations

  • Solid super acidic catalyst and preparation method thereof

    CN101890355A

  • Method for preparing 40% sodium polyaspartate aqueous solution

    CN103554495A